(untitled) (Health Renaissance, 2013)
Background: Though tuberculosis and carcinoma of the bowel are fairly common conditions, the sites of predilection for the two differ, tuberculosis being common in the ileum while carcinoma in the large bowel. Both occurring at the same site is a very rare entity and very few cases have been reported in the literature and none has been recorded in the eastern part of Nepal. Case description: A 35 years old female presented with the complaint of constipation and passage of blood mixed stool since one month. Proctoscopy revealed constricting lesion in the rectum. Provisional diagnosis of carcinoma rectum was made. Histopathological examination showed ulceroinfiltrative lesion in the rectum measuring 11cm in length and extending upto the distal end of sigmoid colon. After microscopic examination a diagnosis of Signet ring cell carcinoma of rectum and sigmoid colon coexisting with tuberculosis was made. Seven lymph nodes dissected from the specimen showed metastatic tumor deposits along with coexisting tuberculous lymphadenitis. Special stain for AFB (TB) and IHC for mucicarmine was positive. Health Renaissance, January-April 2013; Vol. 11 No.1; 162-165 DOI: http://dx.doi.org/10.3126/hren.v11i2.8226